2015
DOI: 10.1155/2015/939748
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Damage Induced by Internal Limiting Membrane Removal

Abstract: The internal limiting membrane (ILM), the basement membrane of the Müller cells, serves as the interface between the vitreous body and the retinal nerve fiber layer. It has a fundamental role in the development, structure, and function of the retina, although it also is a pathologic component in the various vitreoretinal disorders, most notably in macular holes. It was not until understanding of the evolution of idiopathic macular holes and the advent of idiopathic macular hole surgery that the idea of adjuvan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 56 publications
0
44
0
1
Order By: Relevance
“…Controversy focused on the potential side effects of ILM-peeling. Major side effects of ILM peeling have been reported as potential mechanical or functional damage to retina [2][3][4][5][6][7][8][9][10]. Previous studies about retinal functional changes that caused by ILM peeling are conflicting: some studies reported no changes after peeling [11,12], whereas others showed decrease of retinal sensitivity [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Controversy focused on the potential side effects of ILM-peeling. Major side effects of ILM peeling have been reported as potential mechanical or functional damage to retina [2][3][4][5][6][7][8][9][10]. Previous studies about retinal functional changes that caused by ILM peeling are conflicting: some studies reported no changes after peeling [11,12], whereas others showed decrease of retinal sensitivity [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Instead, the pedicle of the ILM attached to the retina allows us to cover the MH in a noninverted way, which would be more physiological. Gelman et al [13] have reviewed some retinal damage induced by ILM removal including damage to müller cell, dissociated optic nerve fiber layer, and phototoxic damage. A number of studies have also investigated the histopathological characteristic of ILM [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Controversy focused on the potential side effects of ILM-peeling. Major side effects of ILM peeling have been reported as potential mechanical or functional damage to retina [2][3][4][5][6][7][8][9][10] . Previous studies about retinal functional changes that caused by ILM peeling are conflicting: some studies reported no changes after peeling [11,12] , whereas others showed decrease of retinal sensitivity [13,14] .…”
Section: Introductionmentioning
confidence: 99%